PERAN PEMERINTAH DESA TERHADAP PEMBANGUNAN DESA KARYA TANI KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR TAHUN 2014-2016 - Muhammad Badri; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Village Government has a significant role in managing social processes in the community. The main task that must be carried out by village government is how to create democratic life, provide good social services so that it can bring its citizens to a prosperous, peaceful and just life. But in reality there is a mismatch between the development plans in Desa Karya Tani. This study aims to determine the role of village government in the development of Karya Tani Village, Kempas District, Indragiri Hilir Regency. The study uses the theory of the role of the Village Government in the Implementation of Development (Taliziduhu Ndraha). Primary information sources (informants) were determined by purposive sampling and the necessary data were collected by interview techniques and literature study. From the results of this study it can be seen that the role of the village government in the implementation of development in the village of peasants' work in the Kempas sub-district of Indragiri Downstream has not run optimally. As for the role of the village head in the implementation of development, namely the ability to make development planning, from the results of research in this Desa Tani Village, the Village Government is quite capable in making village development planning but it's not yet maximal. Ability to provide guidance to subordinates or the community in the implementation of development in Karya Tani Village, Kempas District. The ability to make decisions in the process of organizing development in Karya Tani Village, as well as the ability to coordinate the implementation of development in Karya Tani Village, the ability to oversee activities in the process of carrying out development in Karya Tani Village Keywords: Role, Village Government, Development